2015
DOI: 10.3329/medtoday.v26i2.24223
|View full text |Cite
|
Sign up to set email alerts
|

Different Types of Cardiac Arrhythmias Shown In Holter ECG Monitoring of 100 Patients Studied in NICVD

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…12,23 Another institute based study reported arrhythmia in Holter monitoring was reported in 100 patients from the total, accounting for 67% of the entire sample size. 24 With regards to the incidence of arrhythmia, statistically significant differences were observed for STEMI (40%), NSTEMI (25%) and UA (15%) groups with a p-value less than 0.001. 25…”
Section: Discussionmentioning
confidence: 89%
“…12,23 Another institute based study reported arrhythmia in Holter monitoring was reported in 100 patients from the total, accounting for 67% of the entire sample size. 24 With regards to the incidence of arrhythmia, statistically significant differences were observed for STEMI (40%), NSTEMI (25%) and UA (15%) groups with a p-value less than 0.001. 25…”
Section: Discussionmentioning
confidence: 89%
“…38% of the patients displayed ventricular ectopic, 11% had sick sinus syndrome, 5% had ventricular tachycardia, and 3% had total heart block, according to Faruque et al [12] Just 1% of individuals developed supraventricular ectopic, atrial flutter, atrial fibrillation, or Wolf Parkinson White syndrome.…”
Section: Discussionmentioning
confidence: 91%
“…Arrhythmias were detected frequently in both symptomatic and asymptomatic patients and it is well known that any arrhythmia would cause palpitations now and then so one must be careful to avoid attributing a symptom to an arrhythmia until a close temporal relationship is demonstrated and Holter study was useful tool in this study. 13 In a case report, where a woman complained of palpitation was diagnosed as case of pseudo-AV block a rare rhythm disorder that respond to betablockers. Hereby it seems essential to study palpitation by Holter to reveal rare cardiac rhythm disorder as its etiology.…”
Section: Review Of Literaturementioning
confidence: 99%